Persepsi Masyarakat Terhadap Penerapan Teknologi Tepat Guna Bidang Sumber Daya Air (TTG-BSDA) (Studi Kasus Kabupaten Pacitan, Gunung Kidul Dan Bantul) - Fanani Aziz Alwi; Wildan Herwindo (JURNAL SUMBER DAYA AIR, 2012)
Discharge regulation and measurement in the irrigation scheme are needed to improve water distribution equity and reliability which are often constrained by damaged sluice gates and discharge measuring devices. Sluice gates which are generally made of iron are often damaged because of corrosion or theft. Whereas the discharge measuring devices are often inaccurate because the required flow condition is often eligible and demolished since in the opinion of the farmers these devices are blocking the water flow. In order to solve this problem, a research was conducted to create sluice gates that can be both, a discharge regulator and measuring device. These gates are made of fiberglass/Glass Fiber Reinforced Plastic (GFRP), which is lighter and more corrosion resistant than steel. The shape of this gate is a rounded sluice gate so that it can be used as a measuring device. Tests were then conducted to determine the hydraulic characteristics of flow and discharge formulas that can be used. These tests resulted a contraction coefficient of 0,867 with error rate (Mean Absolute Percentage Error/MAPE) of 3,8% for free flow and 10,4% for submerged flow or an average of 8,71%. This indicates that this rounded sluice gate is feasible to be used as a measuring device. For operational convenience in the field, operators can be equipped with discharge charts or discharge calculators in Java programs that can be operated on a Java MIDP 2.0 cell phone.